86.6k views
2 votes
H(x)=3x−3, find h(3).

User Sptramp
by
5.3k points

2 Answers

5 votes

Answer:

hi

Explanation:

put 3 in place of x . its like a peice of cake

H(x)=3x−3, find h(3).-example-1
User Abu Aqil
by
5.7k points
5 votes

Answer:

h(3) = 6

Explanation:

Given that,

→ x = 3

Then the value of h(3) will be,

→ h(x) = 3x - 3

→ h(3) = 3(3) - 3

→ h(3) = 9 - 3

→ [ h(3) = 6 ]

Hence, the answer is 6.

User AmilaMGunawardana
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.